European Pork Chains : the Role of Stakeholders in Diversification of Quality Management Systems - Szymanowski, Wacław (Olsztyn Economic Journal, 2013)
The paper presents the results of the diagnose concerning the characteristics of pork chains in 6 European Union countries: France, Greece, Spain, The Netherlands, Germany and Hungary. The aim of the paper is to present the differences and fragmentary character of the chains in the pork sector in Europe and diversification of demand for pork products in rapidly developing European markets. Determination of presence of differences in the quality management systems in 6 chosen European countries, i.e. France, Greece, Spain, The Netherlands, Germany and Hungary is the main hypothesis of the paper. Three of those differences apply to specialised pork chains (Spain, The Netherlands and Hungary) while the other three the regional pork chains (France, Greece and Germany). The nature of those chains results from the differences in utilisation of public and private quality management systems and the differences between inter-organisational quality management systems within the chains of supplies strengthening quality cohesion and safety between the links of the chain. The comparison of them allows formulating conclusions for reconstruction of the pork chains in Poland.